Marriage Burnout" Regulation and the Division of Domestic Roles: Finding Progressive Legal Solutions Outside the Conventional Divorce Paradigm - Siti Murni (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2025)
The problem of this research is rooted in a paradox in marriage law. Many couples experience " marriage burnout ," a condition of deep exhaustion that is often triggered by the lopsided division of domestic roles. However, when looking for a solution, the legal system only provides a dead end: endure suffering or divorce. The type of library research or library research. The data collection technique that will be applied is a document study technique from primary and secondary data sources. The research results show that: 1). The deconstruction of marriage burnout as a legal concept is that marriage burnout is not just a personal problem, but a structural injustice. The main root is the lopsided division of domestic roles, where invisible workloads and unequal mental loads create systematic chronic fatigue. 2). Criticism of the Conventional Divorce Lawsuit Paradigm is that the conventional divorce law suit fails completely in dealing with marriage burnout . A legal paradigm centered on "wrongdoing" actually worsens the conflict and does not provide a path for healing, so it only offers a binary solution of survival or divorce, which is insufficient. 3). The Progressive Legal Solution Framework is that as an alternative, the research offers three progressive solutions: (1) Restorative mediation that focuses on the renegotiation of domestic roles, (2) Legal legitimacy for "temporary separation" time as a recovery space, and (3) Therapeutic court orders to create a fairer relationship structure, changing the law from a breaking tool into a facilitator of recovery.